Indications for high-dose chemotherapy with autologous stem cell support in patients with systemic amyloid light chain amyloidosis - Schönland, Stefan; Dengler, Jolanta; Hundemer, Michael; Hegenbart, Ute; Kristen, Arnt; Hund, Ernst; Dengler, Thomas; Beimler, Jörg; Zeier, Martin; Singer, Reinhard; Linke, Reinhold P.; Ho, Anthony Dick; et al. (Transplantation, 2005)
Systemic amyloid light chain amyloidosis is a protein conformation disorder caused by a clonal plasma cell dyscrasia. Symptoms result from fibrillar extracellular deposits in kidney, heart, liver, gut, peripheral nervous system and other tissues. The deposits disrupt organ function and ultimately lead to death. The prognosis of systemic amyloid light chain (AL) amyloidosis is poor; less than 5% of all patients survive 10 years or longer. Using conventional chemotherapy, the median survival could be prolonged by 4 months. Treatment with high-dose melphalm (HDM) and autologous stem cell transplantation (ASCT) of selected patients has been shown to arrest and even to reverse the disease course. This procedure however remains controversial because treatment related mortality (TRM) in AL amyloidosis is substantially higher (15-40%) than in multiple myeloma (<5%). Here we review recent results of ASCT, eligibility criteria for HDM and report our own treatment results in 41 patients.
Gesehen am 04.02.2022